1999
DOI: 10.1111/j.1651-2227.1999.tb00019.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenylketonuria: diet for life or not?

Abstract: Cerone R, Schiaffino MC, Di Stefano S, Veneselli E. Phenylketonuria: diet for life or not? Acta Pædiatr 1999; 88: 664‐6. Stockholm. ISSN 0803‐5253 In order to evaluate the argument whether or not a restricted phenylalanine diet should be maintained for life in patients with phenylketonuria (PKU), 16 patients with early treated PKU but off diet since their 11th birthday were investigated. The evaluation included a detailed neurological examination, IQ, neurophysiological testing and MRI of the brain. Even if IQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 7 publications
0
10
0
1
Order By: Relevance
“…1989; Thompson et al . 1990; MRC Working Party on Phenylketonuria 1993a; Cerone et al . 1999; NIH Consensus Statement 2000) as well as changes in subcortical white matter (Bick et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1989; Thompson et al . 1990; MRC Working Party on Phenylketonuria 1993a; Cerone et al . 1999; NIH Consensus Statement 2000) as well as changes in subcortical white matter (Bick et al .…”
Section: Discussionmentioning
confidence: 99%
“…Our study was unable to consider the quality of life of the patients in the THIN data set because it was a retrospective analysis. Other studies have reported that adults who relax their restricted diet risk developing neurological impairments, such as lack of concentration, poor performance, moodiness, poor spatial ability, defective motor coordination and hyperactivity (Hunt et al 1985;Villasana et al 1989;Thompson et al 1990; MRC Working Party on Phenylketonuria 1993a; Cerone et al 1999;NIH Consensus Statement 2000) as well as changes in subcortical white matter (Bick et al 1991;Thompson et al 1991;NIH Consensus Statement 2000). Some of our observations are concordant with these studies.…”
Section: Resourcementioning
confidence: 99%
“…Neurologically, adults with PKU who were continuously treated but relaxed the treatment diet have displayed white matter abnormalities, identified by structural magnetic resonance imaging (MRI; Bick et al, 1993;Brumm et al, 2004;Cerone, Schiaffino, Di Stefano, & Veneselli, 1999;Cleary et al, 1994;Huttenlocher, 2000;Koch et al, 2002;Leuzzi et al, 2000;Pietz et al, 1998;Sener, 2003;Thompson et al, 1993;Ullrich et al, 1994;Weglage et al, 1997a;Weglage, et al, 1997b;Weglage et al, 1996). These abnormalities have been found adjacent to the ventricle trigones and occipital horns; in the more severe cases the frontal and subcortical white matter have also been implicated.…”
Section: Neurological Symptomsmentioning
confidence: 93%
“…A majority of studies included primarily participants under age 25 at intake (Anastasoaie et al 2008;Azadi et al 2009;Cerone et al 1999;Griffiths et al 2000;Leuzzi et al 1998;Ris et al 1997;Schmidt et al 1994;Seashore et al 1985;Weglage et al 1999Weglage et al , 2000Welsh et al 1990;Viau et al 2011), with five studies including only participants under age 15 at intake (Cerone et al 1999;Griffiths et al 2000;Seashore et al 1985;Weglage et al 1999;Welsh et al 1990). Dietary control varied among the studies, with five studies reporting that all participants adhered to a restricted diet (Anastasoaie et al 2008;Azadi et al 2009;Griffiths et al 2000;Wasserstein et al 2006;Welsh et al 1990), seven reporting a mix of dietary control (some participants on and some off a restricted diet) (Jones et al 1995;Leuzzi et al 1998;Pfaendner et al 2005;Ris et al 1997;Rupp et al 2001;Schmidt et al 1994;Viau et al 2011), and three reporting that participants had discontinued a restricted diet (Cerone et al 1999;S e a s h o r ee ta l1985; Weglage et al 2001). Dietary status was not clearly reported in the remaining studies (Weglage et al 1999(Weglage et al , 2000.…”
Section: Resultsmentioning
confidence: 99%